Opening Routes to Re-Employment Behaviour of Older Women: How do family-related Factors Affect? - Yangkan Yang; Siti Hajar Abu Bakar Ah; Noralina Omar (The Malaysian Journal of Social Administration, 2024)
The number of older workers in urban China who extend their working life after retirement has recently increased, and the proportion of those working older women remains low. This trend underscores the pressing need to address the challenges faced by older women who wish to extend their working lives after the compulsory retirement age. The present study, which focuses on factors impacting the re-employment of older women aged 55 to 70, family-related factors, in particular, is a crucial step towards understanding and addressing this issue. The study is based on pilot data collected from May 2022 to July 2022 among older women individuals in Fuzhou, China, using a self-designed questionnaire. The results reveal that most older women are temporary workers in less skilled sectors such as business and service, agriculture, forestry and fishing, and transport. Furthermore, it is found that re-employed and self-employed women receive a relatively lower monthly pension income compared to fully-retired older women, highlighting the financial implications of their re-employment. Moreover, the research underscores the challenges faced by older women in their re-employment journey. It is found that self-employed older women, despite their higher monthly incomes, still face significant hurdles. Social capital remains the most common avenue for older women to access re-employment after retirement, highlighting the need for stronger support networks. In terms of factors influencing re-employment behaviour, the study reveals that grandchildren care responsibilities, spousal employment, and marital status significantly influence older women’s re-employment behaviour, further emphasizing the complex nature of their situation.